Modelling the distributions of desalination brines from multiple sources along the Mediterranean coast of Israel. (15th April 2020) - Wood, Julie E.; Silverman, Jacob; Galanti, Barak; Biton, Eli
Abstract: We use numerical simulations to study the possible spatiotemporal effects of brine release from five desalination plants, located along the Israeli Mediterranean coastline. It is commonly believed that salinity anomalies, associated with brine discharge from desalination plants, causes effects which are confined to an area of several hundreds of meters from the discharge outfall. We show that discharging brine using diffusers produces small but robust salinity anomalies that propagate tens of kilometers as density currents (DCs). In contrast, premixing the brine with power plant cooling water compensates the negative buoyancy and prevents their generation. The propagating DCs can impact coastal water dynamics by increasing the velocities and transports in alongshore and downslope directions. The spreading and trajectories of the DCs was strongly influenced by seasonal stratification. In winter, due to a mixed water column, the DCs were relatively focused and propagate downslope. While in the summer they are confined to a narrow band along the coastline. Our model results highlight the possibility that brine discharge might have a large scale, non-negligible effect on shelf circulation than previously considered. Further studies are needed to assess the environmental, dynamical and ecological effects of desalination brine propagation, especially in the far field. Highlights: Simulations show density currents are generated when brine is released by diffusers. Dilution with power plant cooling water prevents the development of density currents. The density currents spread widely, increasing alongshore and downslope transport. The propagation of the density currents is affected by seasonal stratification.